The Swimming Performance and Transcriptomic Insights Into Diverse Gene Regulation in Grass Carp Brain Under Water Velocity Stress - Mian Adnan Kakakhel; Nishita Narwal; Alam Khan; Majid Rasta; Liming Liu; Ihsan Ali; Yujiao Wu; Shi Xiaotao (Water Resources Research)
Abstract By linking gene regulation to swimming performance under different water flow conditions, the study could reveal how the fish adapt to their environments, providing insights into evolutionary biology and ecology. The current study observed significant variations in swimming performance under various water flow velocities and examined the associated gene regulation. Grass carp were subjected to controlled water velocities to measure the critical swimming speed (Ucrit), which showed that the swimming performance was increased based on body length; however, a reduction in swimming performance was observed as the water flow increased (p < 0.05). Additionally, brain samples were collected for transcriptomic analysis, which revealed that differentially expressed genes (DEGs) were functionally annotated revealing key pathways associated with changed behavior patterns. The Enrichment analysis showed significant variation in all groups including behavior (p < 0.05***), skeletal system development (p < 0.05***), hormone activity (p < 0.05***), muscle contraction (p < 0.05**), locomotion (p < 0.05*), and swim bladder development (p < 0.05*) were found the major regulators of behavior in grass carp under water velocities. Moreover, some genes were identified and found significantly different for enzymes and hormones, which could play a potential role during swimming performance such as gene‐ca7 (p < 0.005***). The current study provides evidence of the neurogenetic mechanism underlying the changed swimming activity of grass carp under water velocity, which could have important implications for understanding the impact of hydrodynamics and the fish.